Sergio Rotasperti, Metaphors in Proverbs . Decoding the Language of Metaphor in the Book of Proverbs (Supplements to Vetus Testamentum 188; Leiden – Boston, MA: Brill 2021). Pp. XVIII+227. €109.00. ISBN 978-90-04-46410-0 (Hardback), 978-90-04-46605-0 (E-Book) - Targoński, Mateusz Jan (The Biblical Annals, 2022)
Book Review: Sergio Rotasperti, Metaphors in Proverbs. Decoding the Language of Metaphor in the Book of Proverbs (Supplements to Vetus Testamentum 188; Leiden – Boston: Brill 2021).